Goal attainment scaling as an outcome measure in rare disease trials: a conceptual proposal for validation - C. M. W. Gaasterland; M. C. Jansen van der Weide; K. C. B. Roes; J. H. van der Lee (BMC Medical Research Methodology, 2019)
Abstract Background Goal Attainment Scaling (GAS) is an instrument that is intended to evaluate the effect of an intervention by assessing change in daily life activities on an individual basis. However, GAS has not been validated adequately in an RCT setting. In this paper we propose a conceptual validation plan of GAS in the setting of rare disease drug trials, and describe a hypothetical trial where GAS could be validated. Methods We have used the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) taxonomy to deduce which measurement properties of GAS can be evaluated, and how. As individual GAS scores cannot be interpreted outside the context of a RCT, the validation of GAS needs to be done on trial as well as on individual level. Results The procedure of GAS consists of three steps. For the step of goal selection (step 1) and definition of levels of attainment (step 2), face validity may be assessed by clinical experts. For the evaluation of the goal attainment (step 3), the inter and intra rater reliability can be evaluated on an individual level. Construct validity may be evaluated by comparison with change scores on other instruments measuring in the same domain as particular goals, if available, and by testing hypotheses about differences between groups. A difference in mean GAS scores between a group who received an efficacious intervention and a control group is an indication of well-chosen goals, and corroborates construct validity of GAS on trial level. Responsiveness of GAS cannot be evaluated due to the nature of the construct being assessed. Conclusion GAS may be useful as an instrument to assess functional change as an outcome measure in heterogeneous chronic rare diseases, but it can only be interpreted and validated when used in RCTs with blinded outcome assessment. This proposed theoretical validation plan can be used as a starting point to validate GAS in specific conditions.